2019
DOI: 10.3389/fpls.2019.00736
|View full text |Cite
|
Sign up to set email alerts
|

Impact of N, P, K, and Humic Acid Supplementation on the Chemical Profile of Medical Cannabis (Cannabis sativa L)

Abstract: Mineral nutrition is a major factor affecting plant growth and function. Increasing evidence supports the involvement of macro and micronutrients in secondary metabolism. The use of the appropriate nutritional measures including organic fertilizers, supplements, and biostimulants is therefore a vital aspect of medicinal plant production including medical cannabis. Due to legal restriction on cannabis research, very little information is available concerning the effects of nutritional supplements on physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 44 publications
(52 reference statements)
6
111
0
2
Order By: Relevance
“…The amount of cannabinoids formed correlates positively with increased temperatures and imposed heat stress, as well as with low soil moisture and poor mineral nutrient content [31,32]. The latter was indicated by a negative correlation between mineral supply and cannabinoid production [33,34]. Cannabinoid production may also provide an evolutionary advantage by functioning as sun-C2 carbon units derived from malonyl-CoA.…”
Section: Sites Of Phytocannabinoid Biosynthesis and Their Possible Fumentioning
confidence: 99%
“…The amount of cannabinoids formed correlates positively with increased temperatures and imposed heat stress, as well as with low soil moisture and poor mineral nutrient content [31,32]. The latter was indicated by a negative correlation between mineral supply and cannabinoid production [33,34]. Cannabinoid production may also provide an evolutionary advantage by functioning as sun-C2 carbon units derived from malonyl-CoA.…”
Section: Sites Of Phytocannabinoid Biosynthesis and Their Possible Fumentioning
confidence: 99%
“…A study reported that P uptake by hemp ranged from 52 to 67 kg ha −1 , and P fertilization had no effect on stem yield [67]. P enhancement treatment caused a 16% reduction of THC concentration but did not affect CBD concentration in the flowers [71]. P deficiency can also affect hemp ability to uptake other essential nutrients, and can subsequently reduce the plant health, immunity to disease, crop quality, and yield.…”
Section: Effect Of Phosphorusmentioning
confidence: 99%
“…The natural phytocannabinoids and terpenoids present in Cannabis are biosynthesized in the plant by specific enzymes. The compositions and concentrations of these molecules depend on the plant’s tissue-type, age, variety, growth conditions and harvest time ( Berman et al, 2018 ; Hawley et al, 2018 ; Welling et al, 2018 ; Bernstein et al, 2019a , b ; Namdar et al, 2019 ). Importantly, they also change over time postharvest, as a result of different degradation routes ( Trofin et al, 2011 , 2012 ; Peschel, 2016 ; Zamengo et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%